Dense graded hot mixes using asphalt-rubber binders with high rubber contents - Neto, Silvrano Adonias Dantas (2006)
This paper shows the results of a study about the mechanical behavior of dense graded asphalt-rubber hot mixes prepared with two different types of asphalt-rubber binders. These asphalt-rubber binders were obtained with penetration grade asphalt (AC 50/70) mixed with 21% and 25% of crumb rubber in weight. The rubber was recycled from unserviceable tires using the ambient grinding process. Hot mixes made with the conventional binder AC 50/70 were also studied for comparison. The mechanical behavior of hot mixes was evaluated through laboratory tests for fatigue life, permanent deformation and indirect tensile strength. The results showed that asphalt-rubber hot mixes presented better mechanical behavior for fatigue life and permanent deformation than those obtained with the straight binder. © 2006 Taylor & Francis Group, LLC. All rights reserved.